The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/bf03052500
|View full text |Cite
|
Sign up to set email alerts
|

Shapley inequality decomposition by factor components: Some methodological issues

Abstract: Shapley Value, Inequality, Decomposition, D31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 5 publications
0
58
0
5
Order By: Relevance
“…These remarks have permitted the elaboration of a set of strong criticisms against the Shapley-shorrocks and its applicability to the analysis of inequality by sources, criticisms that can be found in summary in the article of Sastre and Trannoy (2002). The latter proposes the nested form of Shapley decomposition basing on the extensions brought by Owen (1977) to the original value of Shapley.…”
Section: Appendicesmentioning
confidence: 99%
“…These remarks have permitted the elaboration of a set of strong criticisms against the Shapley-shorrocks and its applicability to the analysis of inequality by sources, criticisms that can be found in summary in the article of Sastre and Trannoy (2002). The latter proposes the nested form of Shapley decomposition basing on the extensions brought by Owen (1977) to the original value of Shapley.…”
Section: Appendicesmentioning
confidence: 99%
“…Using the concept of Shapley decomposition (see, Shorrocks, 1999, Sastre andTrannoy, 2002, and Appendix B, for more details), …”
Section: 1mentioning
confidence: 99%
“…It is assumed that there is no change over time in the poverty line z. Using the concept of Shapley decomposition 6 (see, Shorrocks, 1999, andSastre andTrannoy, 2002, as well Appendix B, for more details on this decomposition) it can be shown that the relative change in poverty ) / ( θ θ d may be expressed as the sum of two components, one, Gr, reflecting the impact of growth, inequality remaining constant, and the other, In, measuring the effect of a change in inequality, the mean income staying constant, that is…”
Section: Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a function need not be linear. Although Chantreuil and Trannoy (1999) and Sastre and Trannoy (2002), who came up with the idea of Shapley decomposition, limited their application of the Shapley value to the decomposition of income inequality, Shorrocks (1999) has shown that such a decomposition could be applied to any function. The idea of the Shapley value is to consider all the possible sequences allowing us to eliminate the variables a and b.…”
Section: The Shapley Decomposition and Its Implications For Multidimementioning
confidence: 99%